Getting Into the Brain: The Intranasal Approach to Enhance the Delivery of Nerve Growth Factor and Its Painless Derivative in Alzheimer’s Disease and Down Syndrome - Capsoni, Simona; Cattaneo, Antonino (Frontiers in Neuroscience, 2022)
The neurotrophin Nerve Growth Factor (NGF) holds a great potential as a therapeutic candidate for the treatment of neurological diseases. However, its safe and effective delivery to the brain is limited by the fact that NGF needs to be selectively targeted to the brain, to avoid severe side effects such as pain and to bypass the blood brain barrier. In this perspective, we will summarize the different approaches that have been used, or are currently applied, to deliver NGF to the brain, during preclinical and clinical trials to develop NGF as a therapeutic drug for Alzheimer’ s disease. We will focus on the intranasal delivery of NGF, an approach that is used to deliver proteins to the brain in a non-invasive, safe, and effective manner minimizing systemic exposure. We will also describe the main experimental facts related to the effective intranasal delivery of a mutant form of NGF (painless NGF, hNGFp) in mouse models of Alzheimer’s disease and compare it to other ways to deliver NGF to the brain. We will also report new data on the application of intranasal delivery of hNGFp in Down Syndrome mouse model. These new data extend the therapeutic potential of hNGFp for the treatment of the dementia that is progressively associated to Down Syndrome. In conclusion, we will show how this approach can be a promising strategy and a potential solution for other unmet medical needs of safely and effectively delivering this neuroprotective neurotrophin to the brain.